DAMPAK KONSERVATISME AKUNTANSI DAN STRUKTUR KEPEMILIKAN TERHADAP RELEVANSI INFORMASI AKUNTANSI - Fuad, Fuad (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2012)
This study aims to figure out the impactof ownershipstructure and accounting conservatism on thevalue relevance of accounitng information. Besides, this study also tests the efficiency of return inreflecting firms’ future profitability. Results of the study imply that firms with higher institutionalownership has more capability in predicting future profitability. Finally, current study alsofiguresout that the information content of accounting information is slightly faster in the firms withmore conservative accounting policies.Keyword:accounting conservatism, ownership structure, accounting information